Population Genetics Data of 21 Autosomal STR Loci in the Romanian Population - George Popoiu; Florin Stanciu; Veronica Cuțăr; Simona Vladu; Paulina Podgoreanu; Violeta Nicola; Ionel Marius Stoian; Anastasia Procopciuc; Bogdan Hațegan; Bogdan Negoiță; Alis Mihaela Păunache; Adnana Cotolea; et al. (Data)
This study aimed to determine the allele frequencies and genetic diversity of 21 autosomal short tandem repeat (STR) loci from the Expanded U.S. Core Loci and European Standard Set in the Romanian population. A random sample of 928 unrelated men from all Romanian counties was analyzed using the Investigator 24plex QS and Investigator 24plex GO! Kits (Qiagen). The genotypes were determined, and the allele frequencies were calculated using the STRidER tool. The results provide updated population genetic data for the Romanian population, which is essential for accurate calculation of DNA evidence weight in forensic casework.